PEMBANGUNAN PEMERINTAHAN MADINAH MELALUI PEMIKIRAN DAN USAHA INTELEKTUAL PERSPEKTIF PERADABAN ISLAM MASA NABI MUHAMMAD SAW - Irfan Fauzi; Abdul Mukti; Zaini Dahlan (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2021)
Civilization can only be built through a strong and mature leadership process. The Prophet Muhammad SAW as a leader was able to show evidence that he was able to build a pluralistic, heterogeneous and pluralistic social order of society, especially in the city of Medina where basically the people of the city highly uphold these values. Driven by the spirit of Islam, Prophet Muhammad SAW moved and fought as a revolutionary who succeeded in bringing Islam into a perfect religion to be accepted by the people of Medina. This can be seen from a major event which became known as the Medina Charter. The Hijrah agenda is a benchmark for the existence of Islam in conveying messages of peace starting from the city of Medina. This research was conducted with a Library Research approach and searches from journals and scientific articles with the aim of producing accurate and scientifically accountable research.